Pembuatan Permainan Adventure Brain Challenge - Yoemakna, Cahyadi; Purba, Kristo Radion; Santoso, Leo Willyanto (Jurnal Infra, 2015)
Utilization of appropriate technologies and strategies will improve learning outcomes optimally. Many jobs in the education world by computer-assisted work, ranging from typing, math, browsing on the internet, and as a media of learning. The term learning media can be regarded as a tool for learning. Therefore made the game media to increase public knowledge and can also be a means for entertainment.In this study designed a game that has some features and mini-games. The measures include moving system making level, features mini-games, load and save system, collision detection with bounding box method, NPC, and set items. Applications created using ActionScript 3.0 programming language and Adobe Flash CS6 as IDE. The result showed the success of the mini-games, thoroughness and diligence in designing a map, display of objects, as well as gaming systems affect the final outcome of the application. The number of objects and the more detailed the manufacture and preparation of the object will increasingly make the game even more interesting.